Przekład — kontekst — polityka. Próba lektury Rozważań o Polsce Draga Jančara - Kopczyk, Michał (Przekłady Literatur Słowiańskich, 2020)
This article discusses Drago Jančar’s 1997 essay, Adam Michnik ali premišljevanje o Poljski (Adam Michnik; Or, Reflections on Poland). The essay was translated into Polish first by Joanna Pomorska (2001) and then, about two decades later, by Nikodem Szczygłowski. The aim of the article is to interpret Jančar’s essay in light of ongoing changes to the political situation in Europe and to evaluate to what extent the political context influences the interpretation of the work in question.